Descriptive epidemiology of hip and knee replacement in rheumatoid arthritis: an analysis of UK electronic medical records - Hawley, S; Edwards, C; Arden, N; Delmestri, A; Cooper, C; Judge, A; Prieto Alhambra, D (Elsevier, 2019)
Objective: To provide descriptive data on rates of total hip replacement (THR) and total knee replacement (TKR) within a large RA cohort and describe variation in risk. Methods: Incident RA patients (1995 to 2014) were identified from the Clinical Practice Research Datalink (CPRD). First subsequent occurrence of THR and TKR were identified (analysed separately) and incidence rates calculated, stratified by sex, age, BMI, geographic region, and quintiles of the index of multiple deprivation (IMD) score. Results: There were 27,607 RA patients included, with a total of 1,028 THRs (mean age at surgery: 68.4 years) and 1,366 TKRs (mean age at surgery: 67.6 years), at an overall incidence rate per 1,000 person-years (PYs) [95% CI] of 6.38 [6.00 - 6.78] and 8.57 [8.12 - 9.04], respectively. TKR incidence was similar by gender but THR rates were higher in females than males. Rates of TKR but not THR rose according to BMI. An increasing trend was observed in rates of both outcomes according to age (although not ≥75) but of decreasing rates according to socio-economic deprivation. There was some evidence for regional variation in TKR. The 10-year cumulative incidence was 5.2% [4.9, 5.6] and 7.0% [6.6, 7.4] for THR and TKR, respectively. Conclusion: We provide generalizable estimates of THR and TKR incidence in the UK RA patient population and note variation across several key variables. Increased BMI was associated with a large increase in TKR but not THR incidence. Increased deprivation was associated with a downward trend in rates of THR and TKR.